Improving Rehabilitative Care of Methamphetamine Users in Germany: The Expert's Perspective. (January 2019) - Hoffmann, Laura; Buchenauer, Lisa; Schumann, Nadine; Schröder, Sara Lena; Martin, Olaf; Richter, Matthias
Methamphetamine is one of the most frequently used drugs worldwide. In Germany, methamphetamine use has greatly increased in recent years, presenting the rehabilitative treatment system with new challenges. In this study, we identified deficits and possibilities for optimization in the field of medical rehabilitation. A total of 39 interviews and two focus groups with experts along the treatment course of methamphetamine users were conducted. Our analyses indicate that methamphetamine users are more difficult to treat compared with patients who consume other drugs. They are more likely to be associated with problematic characteristics and behaviors than other rehabilitants. Several health care deficits were revealed: too short rehabilitation treatment, no specific or differentiated therapy concepts, lack of capacity for education and vocational training, lack of outpatient options, and insufficient facilities for parents and children. Findings indicate that inadequate rehabilitation is being provided for methamphetamine users in Germany, indicating a need to adapt treatment for this group.